Kontribusi Pendidikan Islam terhadap Pengembangan Jiwa Kepemimpinan pada Generasi Muda - Rani Puspita; Habibah Maulida; Gusmaneli Gusmaneli (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
Leadership in Islam has a broad scope, involving spiritual, moral, and social aspects. An ideal leader in Islam must not only have good managerial skills, but also integrity, noble morals, and responsibility towards society. Islamic education plays an important role in shaping the character of leaders with integrity through teaching moral values, social responsibility, and leadership skills. The integration of Islamic values ​​in the curriculum and extracurricular activities is expected to produce leaders with strong character and abilities. The role of teachers and educational institutions is crucial in creating an environment that supports the development of leadership in the younger generation, so that it can produce future leaders who are not only technically skilled, but also have integrity and are ready to bring positive change to society.